2011
DOI: 10.2500/ajra.2011.25.3600
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Single-blinded Controlled Trial on Biodegradable Synthetic Polyurethane foam as a Packing Material after Septoplasty

Abstract: SPF is as suitable as Merocel to be used after septoplasty with beneficial effects on bleeding and pain at packing removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 10 publications
0
45
0
Order By: Relevance
“…A total of 459 potentially relevant articles were identified from the initial search; however, most were retrospective studies, review articles, non-randomized studies, case reports, or not relevant to the aim of the present study, or provided irrelevant data. Ultimately, seven trials [6]–[8], [11]–[14] were identified as eligible, all of which were RCTs published from 2009 to 2013, and consensus on study selection was reached by discussion among the researchers. Characteristics of eligible trials are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 459 potentially relevant articles were identified from the initial search; however, most were retrospective studies, review articles, non-randomized studies, case reports, or not relevant to the aim of the present study, or provided irrelevant data. Ultimately, seven trials [6]–[8], [11]–[14] were identified as eligible, all of which were RCTs published from 2009 to 2013, and consensus on study selection was reached by discussion among the researchers. Characteristics of eligible trials are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…One trial reported allocation concealment with a sealed envelope [6], but concealment of allocation was an undefined risk in the other studies because it was not reported. Double blinding method was applied in one study [8], single blinding of patients in two [6], [12], and unmasked designation in one [7], blinding was not reported in the remaining three [11], [13], [14]. Funding biases were not evident in any of the studies, and they did not have baseline imbalances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, during the removal of the Merocel packing, the possibility of bleeding from the epithelium is increased as bloody crusts or blood clots present between the Merocel packing and the nasal mucosa may be removed at the same time, which would result in more crusting and the formation of granulation tissue. 32 Several other studies have reported that using FS for endonasal surgeries, including septoplasty and conchotomy, is effective in producing postoperative hemostasis. 25,26,[34][35][36] Gleich et al 37 found that autologous fibrin tissue adhesives provided reliable hemostasis, decreased crusting, accelerated mucosal healing, and diminished synechiae.…”
Section: Discussionmentioning
confidence: 99%
“…Many forms of nasal packing are available, including Merocel, "rapid rhino", the "Doyle pack", gauze with vaseline, and synthetic polyurethane. These are placed after surgery to prevent bleeding, septal hematoma, and septal abscess (13,14). Although the packs afford many advantages, they increase the risk of infection and cause pain (15).…”
Section: Discussionmentioning
confidence: 99%